Direct-Acting Antiviral Treatment of HCV Infection Does Not Resolve the Dysfunction of Circulating CD8+ T-Cells in Advanced Liver Disease - Vranjkovic, Agatha; Deonarine, Felicia; Kaka, Shaima; Angel, Jonathan B.; Cooper, Curtis L.; Crawley, Angela M. (Frontiers in Immunology, 2019)
Chronic hepatitis C virus (HCV) infection disrupts immune functions, including that of cytotoxic CD8+ T-cells which are important mediators of immune response. While HCV cure aims to eliminate long term sequelae of infection, whether direct-acting antiviral (DAA) treatment results in immune reconstitution remains unclear. We and others have reported generalized CD8+ T-cell dysfunction in chronic HCV infection and our research suggests that the degree of liver damage is a factor in this process. Our recent research indicates that liver fibrosis is not readily reversed after DAA-mediated clearance of chronic HCV infection. We therefore examined the function of circulating CD8+ T-cell subsets in chronic HCV infection in the context of liver fibrosis severity, determined by ultrasound elastography and Metavir F-score system. We observed progressive shifts in CD8+ T-cell subset distribution in HCV-infected individuals with advanced liver fibrosis (F4) compared to minimal fibrosis (F0-1) or uninfected controls, and this remained unchanged after viral cure. Impaired CD8+ T-cell function was observed as a reduced proportion of CD107+ and perforin+ late effector memory cells in HCV+(F4) and HCV+(F0-1) individuals, respectively. In HCV+(F4) individuals, nearly all CD8+ T-cell subsets had an elevated proportion of perforin+ cells while naïve cells had increased proportions of IFN-+ and CD107+ cells. These exaggerated CD8+ T-cell activities were not resolved when evaluated 24 weeks after completion of DAA therapy and HCV clearance. This was further supported by sustained, high levels of cell proliferation and cytolytic activity. Furthermore, DAA therapy had no effect on elevated concentrations of systemic inflammatory cytokines and decreased levels of inhibitory TGF-β in the plasma of HCV+(F4) individuals, suggesting HCV infection and advanced liver disease result in a long-lasting immune activating microenvironment. These data demonstrate that in chronic HCV infection, liver fibrosis severity is associated with generalized hyperfunctional CD8+ T-cells, particularly with perforin production and cytotoxicity, and this persists after viral clearance. Whether DAA therapy will eliminate other related long-term sequelae in HCV+(F4) individuals remains an important research question.